Combined Spraying of Boron and Zinc During Fruit Set and Premature Stage Improves Yield and Fruit Quality of European Hazelnut cv. Tonda di Giffoni - Meriño-Gergichevich, Cristian; Luengo-Escobar, Ana; Alarcón, David; Reyes-Díaz, Marjorie; Ondrasek, Gabrijel; Morina, Filis; Ogass, Khristopher (Frontiers in Plant Science, 2021)
Boron (B) and zinc (Zn) are essential micronutrients of plant nutrition programs in orchards for securing the crop quality and yield. Although orchard supplementation with B and Zn is a common practice to overcome deficiencies or maintain their optimal levels, the efficiency of combined B and Zn spraying in relation to European hazelnut (Corylus avellana L.) phenological stage has not been investigated so far. Leaf and kernel mineral and functional traits were studied in cultivar Tonda di Giffoni after B and Zn spraying in four phenological stages. During the 2016/2017 season, 9-year-old trees were sprayed with B (0, 800, and 1,600 mg L−1) and Zn (0, 400, and 800 mg L−1) under three treatments: B0+Zn0, B800+Zn400, and B1600+Zn800 implemented in three spring application programs scheduled from October to December (P1: four times, P2: early two times, and P3: late two times). B and Zn treatments in P1 and P3 led to higher Zn concentration both in leaves and in kernels compared with non-sprayed trees. Stabilized nut production increased 2.5-fold under B800+Zn400 in all three programs. Kernel/nut ratio improved in both B+Zn treatments in P1 and P3, while the percentage of blank nuts was reduced compared with B0+Zn0. Increased radical scavenging activity in B+Zn-treated kernels and leaves was not attributed to the accumulation of phenolics in P3 compared with B0+Zn0, whereas B and Zn spraying reduced the level of lipid peroxidation in both studied organs. According to the results, combined B and Zn should be sprayed at the end of spring (P3) on hazelnut plantations in temperate areas such as Southern Chile, whereas early applications (P2) showed an irregularity in nut production and functional traits in nuts. Moderate and partialized rates of B and Zn and the time of implementation contribute to improving the quantitative and qualitative features crucial for future sustainable hazelnut production.